2016
DOI: 10.1016/j.fsigen.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Massively parallel sequencing of short tandem repeats—Population data and mixture analysis results for the PowerSeq™ system

Abstract: Current forensic DNA analysis predominantly involves identification of human donors by analysis of short tandem repeats (STRs) using Capillary Electrophoresis (CE). Recent developments in Massively Parallel Sequencing (MPS) technologies offer new possibilities in analysis of STRs since they might overcome some of the limitations of CE analysis. In this study 17 STRs and Amelogenin were sequenced in high coverage using a prototype version of the Promega PowerSeq™ system for 297 population samples from the Nethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(84 citation statements)
references
References 17 publications
4
74
1
Order By: Relevance
“…PCR products were purified using Wizard SV Gel and PCR Clean-Up System kit (Promega Corporation). For targeted NGS on cDNA, libraries were prepared from PCR products by ligating barcoded TruSeq adapters (Illumina) using the KAPA Library Preparation kit (KAPA Biosystems) [18]. After pooling the libraries, sequencing was performed on the MiSeq sequencer (Illumina) using v3 sequencing reagents according to the manufacturer's protocol.…”
Section: Validation Of Hamlet Outputmentioning
confidence: 99%
“…PCR products were purified using Wizard SV Gel and PCR Clean-Up System kit (Promega Corporation). For targeted NGS on cDNA, libraries were prepared from PCR products by ligating barcoded TruSeq adapters (Illumina) using the KAPA Library Preparation kit (KAPA Biosystems) [18]. After pooling the libraries, sequencing was performed on the MiSeq sequencer (Illumina) using v3 sequencing reagents according to the manufacturer's protocol.…”
Section: Validation Of Hamlet Outputmentioning
confidence: 99%
“…As is common practise in forensic genetics, such novel tools undergo detailed evaluation [3,[8][9][10][11][12] and validation [1,13,14] prior to their application in casework. Recent population studies have shown that sequencing of STRs lead to an increased power of discrimination compared to commonly used CE sizing by a) illustrating micro-variant structures and b) identifying sequence variations located in the repeat-(isometric variants; alleles of identical size but different in internal sequence) or flanking region [15][16][17][18][19][20]. Moreover, current MPS-kits provide the option to multiplex various loci simultaneously within one reaction, such as STRs (autosomal, Y-and X-chromosomal), mitochondrial DNA (control region) as well as single nucleotide polymorphisms (SNPs) that provide estimates of identity, phenotypic traits, biogeographical and ancestry information [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NGS has potential advantages with challenging samples and complicated familial testing (6,8,9). Therefore, increasing numbers of research groups are dedicating substantial efforts to studying NGS-based STR genotyping (10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Bornman et al's (5) study on short-read STR genotyping was an exception. Since 2015, the research community has shifted work to Miseq (7,11,12,14,16,(23)(24)(25)(26)(27) and Ion Torrent NGS machines (9,10,13,15,28) because 454 sequencers are no longer supported by their producer. Typing results for 48 autosomal STR markers (11,12,22,24), 29 Y-STR markers (10,24,25), and 9 X-STR markers (24) have been reported.…”
mentioning
confidence: 99%